2010
DOI: 10.1063/1.3482017
|View full text |Cite
|
Sign up to set email alerts
|

On the electric polarization of inhomogeneous superfluid systems

Abstract: The electric polarization appearing in superfluid systems as a result of their inhomogeneity is studied. The problem is studied using the rarefied electron-hole gas model which the authors studied previously. A microscopic calculation is performed of the polarization of quantum vortices in the absence and presence of a magnetic field. It is established that in the presence of a magnetic field vortices acquire additional polarization, which results in the appearance of a quantized charge in a vortex core. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…2 and 17) and in terms of the two-particle order parameter U(r 1 , r 2 ). [18][19][20][21] It is found that there are fundamental differences between these two approaches. In applying the first method to composite bosons the effects related to the exchange interaction are completely lost, which in some cases, particularly in the case of the Coulomb interaction between the particles, leads to qualitatively incorrect results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 and 17) and in terms of the two-particle order parameter U(r 1 , r 2 ). [18][19][20][21] It is found that there are fundamental differences between these two approaches. In applying the first method to composite bosons the effects related to the exchange interaction are completely lost, which in some cases, particularly in the case of the Coulomb interaction between the particles, leads to qualitatively incorrect results.…”
Section: Resultsmentioning
confidence: 99%
“…It is easy to see that the operatorsb þ k andb k satisfy the commutation relations different from Bose ones. They satisfy the Bose statistics for k 6 ¼ k 0 and the Pauli principlê 26 The authors in a number of works, [18][19][20][21] developing the approach of Keldysh, studied properties of dilute electronhole systems, caused by their internal structure. In this section we generalize the theory from Refs.…”
Section: A Coherent State Of Fermion Pairsmentioning
confidence: 99%
See 1 more Smart Citation
“…Macroscopic spatial separation of the vortex charge and the compensating one allows to measure the electric field caused by these charges and to observe the motion of vortices in the superfluid. In this message we discuss the significant aspects of measuring the electric fields generated by the vortices.First we recall the arguments of the articles [14] - [16]. In a magnetic field H a rarefied medium moving with velocity v acquires polarizationHere α is the atom polarizability, n is the medium den- * Electronic address: shevchenko@ilt.kharkov.ua sity, c is the velocity of light.…”
mentioning
confidence: 99%
“…In articles [41][42][43] polarization phenomena in 3D superfluid gas of electron-hole pairs (without spatial separation of electrons and holes) have been analyzed using an approach based on Keldysh's function. In [44] the Keldysh's approach has been applied to description of the superfluid state of a rarefied gas formed by alkali metal atoms.…”
Section: Introductionmentioning
confidence: 99%